Mineral resource estimation of the Brockman 4 iron ore deposit in the Pilbara region. (June 2014) - Sommerville, B.; Boyle, C.; Brajkovich, N.; Savory, P.; Latscha, A.-A.
<x content-type="archive" xml:space="preserve">Abstract</x> Brockman 4 is a large iron ore deposit hosted by the Brockman Iron Formation in the Pilbara region and is mined by Rio Tinto Iron Ore. Drilling is mainly by the reverse circulation method and samples are taken at 2 m intervals using a rotary cone splitter or historically by riffle splitter. Samples are geologically logged, assayed by X-ray fluorescence for iron, silica, alumina, phosphorus, manganese, sulphur, titanium oxide, calcium oxide, magnesium oxide, and 19 other trace elements; and measured for loss on ignition by thermogravimetric analysis. Mineralisation is estimated by ordinary kriging with unfolding and waste by inverse distance interpolation. The model is validated, reconciled with historic production, classified according to the 2012 Edition of the JORC code and stored in a SQL Server database.